Discovery of structurally distinct tricyclic M4 positive allosteric modulator (PAM) chemotypes – Part 2. (1st December 2021) - Long, Madeline F.; Capstick, Rory A.; Spearing, Paul K.; Engers, Julie L.; Gregro, Alison R.; Bollinger, Sean R.; Chang, Sichen; Luscombe, Vincent B.; Rodriguez, Alice L.; Cho, Hyekyung P.; Niswender, Colleen M.; Bridges, Thomas M.; et al.
Graphical abstract: Abstract: This Letter details our efforts to develop novel tricyclic M4 PAM scaffolds with improved pharmacological properties. This endeavor involved a "tie-back" strategy to replace the 3-amino-4, 6-dimethylthieno[2, 3- b ]pyridine-2-carboxamide core which lead to the discovery of two novel tricyclic cores: a 7, 9-dimethylpyrido[3′, 2′:4, 5]thieno[3, 2-d]pyrimidine core and 2, 4-dimethylthieno[2, 3- b :5, 4-c′]dipyridine core. Both tricyclic cores displayed low nanomolar potency against the human M4 receptor.